Evaluation of umbilical cord serum therapy for persistent corneal epithelial defects. Issue 11 (10th November 2003) - Vajpayee, R B; Mukerji, N; Tandon, R; Sharma, N; Pandey, R M; Biswas, N R; Malhotra, N; Melki, S A
Abstract : Aims: To evaluate umbilical cord serum therapy as a means of promoting the healing of persistent corneal epithelial defects. Methods: Umbilical cord serum or autologous serum drops were used to promote the healing of persistent epithelial defects. The study design was a prospective randomised controlled clinical trial. 60 eyes of 59 patients were divided into two groups, 31 in the cord serum group and 29 in the autologous serum control group. Epithelial defects measuring at least 2 mm in linear dimension resistant to conventional medical management were included. Serial measurements of the size of the epithelial defects—namely, two maximum linear dimensions perpendicular to each other, and the area and perimeter was done at start of therapy and follow up days 3, 7, 14, 21. Rate of healing of the epithelial defects were measured as percentage decrease from the baseline parameter at each subsequent follow up. The data were analysed by the non-parametric Wilcoxon rank sum test using STATA 7.0. Results: The median percentage decrease in the size of the epithelial defect was significantly greater in the cord serum group at days 7, 14 and 21 (p<0.05) when measured in terms of the area and perimeter. A greater number of patients showed complete re-epithelialisation with umbilical cord serum (n = 18) than with autologous serum (n = 11) (Pearson χ = 0.19). None of the patients reported any side effects or discomfort with either treatment. Conclusions: Umbilical cord serum leads to faster healing of the persistent corneal epithelial defects refractory to all medical management compared to autologous serum.